'China's Emergence as a Power in the Mediterranean: Port Diplomacy and Active Engagement'. Issue 2 (3rd April 2021) - Rhode, Grant F.
ABSTRACT: In the decade between 2009 and 2019, China emerged as an economic power with geostrategic dimensions in the Mediterranean and Southeastern Europe, a region contested by great powers for many centuries. After firmly establishing primacy in the Greek port of Piraeus, China has executed a sweeping programme of port diplomacy involving over two dozen ports along Mediterranean European, Middle Eastern, and North African shores. Concurrently, China has conducted a programme of active engagement with the Central and Eastern European Countries, resulting in the 17 + 1 association tied to its Belt and Road Initiative through the Mediterranean Piraeus gateway. Based on these developments, China is well situated to expand its power in the Mediterranean going forward.